SEMANTIC CHARACTERISTICS OF HYDROTOPONYMS, ZOOMORPHIC AND ETHNOPONYMS IN GERMAN AND UZBEK LANGUAGES - Axmedova Dildora Jo’raxon Qizi (American Journals, 2023)
This article studies the semantic features of hydronyms, toponyms with a zoomorphic component, and ethnotoponyms in German and Uzbek languages. The similarities in naming the place names of the German and Uzbek peoples are considered.
Keywords: German and Uzbek toponyms, hydrotoponyms, zoomorphic and ethnotoponyms, Wasserburg, Wasserberg, Herborn, Eulenburg, Rabensburg, Tataredellche, Franzosengraben, Oltinsoy, Arnasoy, Kushbegi, Kuyonkulok, Mangit, Naymantepa.